Segurança hídrica que vem do mar: quanto você estaria disposto a pagar? - Cavalcante, Maria Regiane Araújo (2024)
The growing global water scarcity has driven the search for innovative solutions, such as seawater desalination, to face challenges in public supply. In Fortaleza, Ceará, a seawater desalination plant, DESSAL project, is being implemented, with the aim of providing water for human consumption. However, the economic viability of water security projects is influenced by users' Willingness to Pay (WTP), which in turn, is closely linked to the individual's intentions and perceptions of control, according to the Theory of Planned Behavior (TPB) and the Perceived Value (PV) of the initiative. In this context, the general objective of this study is to analyze the background and willingness to pay of the population of Fortaleza for supplying desalinated seawater. To this end, the study used the Contingent Valuation Method to evaluate the willingness to pay for the supply of desalinated seawater in Fortaleza, from three perspectives: use of desalinated seawater to improve the quality and conditions of water supply, to ensure water security and preservation of the State’s water resources. The study is quantitative in nature and as data collection instruments, bibliographical research, document analysis and application of 184 questionnaires were carried out, with users residing in Fortaleza. To estimate the respondents' WTP, the free throw format was used. Statistical analysis was performed using Structural Equation Modeling and Cluster Analysis using the K-means method. According to the findings in the results, the relationships between Perceived Value and Attitude, Subjective Norm for Government and Media, Subjective Norm for People, and Perceived Behavioral Control are remarkably significant. Furthermore, the link between Perceived Behavioral Control and Willingness to pay is significant at the 0.05 level. The highest DAP, 8.07%, was observed to ensure water security, followed by the WTP to improve the quality and conditions of water supply for the respondent's family, with 8.05%, and, finally, the WTP reported for ensuring the conservation of the State's water bodies was 7.69% more than the monthly household water tariff. Seven distinct clusters were identified, reflecting a wide range of dispositions and demographic characteristics, where the coefficient of determination of the clusters is 52.4%.